What Drives E-Wallet Usage in Bekasi Regency? The Roles of Perceived Security and Fintech Trust - Devi Yuliati Ratnasari; Elsye Fatmawati (Lentera Ilmu Nusantara, 2026)
The development of financial technology has driven a significant transformation in payment systems from cash-based transactions to more efficient and practical digital payments. One of the fintech innovations experiencing rapid growth in Indonesia is the electronic wallet (e-wallet). Although e-wallet adoption continues to increase, the sustainability of usage behavior is strongly influenced by users' perceptions and attitudes toward system security and risk. This study aims to examine the effect of perceived security and trust in fintech on e-wallet usage behavior among residents of Bekasi Regency. This research employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 110 e-wallet users in Bekasi Regency. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that perceived security has a positive and significant effect on e-wallet usage behavior, while trust in fintech shows a positive but insignificant effect. Collectively, perceived security and trust in fintech explain 47.8% of the variance in e-wallet usage behavior. These findings suggest that security perception is the dominant factor influencing e-wallet usage, whereas trust in fintech requires longer-term experience to exert a significant impact.